(untitled) (Asian Journal of Social Science Studies, 2022)
The financing methods mainly include internal financing and external financing and different financing methods have different effects on performance. As an important part of the capital structure, the debt financing structure will not only affect the profit level of the enterprise, but also affect the external investors of the enterprise through signal transmission and then have an impact on the performance of the enterprise. Based on this background, it is particularly important to study whether debt financing can bring corresponding performance improvement to enterprises. Therefore, this paper selects Chinese A-share listed companies as the research sample and uses the panel data from 2016 to 2020 as the basis to use regression to conduct an empirical test on the impact of Chinese A-share listed companies’ debt financing on corporate performance. The results show that there is a significant negative correlation between debt financing of Chinese A-share listed companies and corporate performance. Based on this empirical result, this article puts forward corresponding improvement suggestions, which will help promote the improvement of corporate performance.